Quality Improvement Efforts of DGT’s Internal Compliance Unit (Study at Yogyakarta Small Tax Office) - Anika Mailina; Bachrudin K. Una; Hendi Yogi Prabowo (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2024)
The Internal Control System is implemented in the organization as a prevention of fraud risk. The Directorate General of Taxes (DGT) already has an Internal Compliance Unit (hereinafter referred to as UKI) as the vanguard in internal control efforts. However, there are still cases of fraud and Hand-Arrest Operations at the DGT that have questioned the quality of UKI. This study aims to find the constraints experienced by UKI in carrying out internal control monitoring tasks as well as efforts that can be made to improve the quality of UKI. This research method is qualitative with a case study at the Yogyakarta Small Tax Office (STO). The types of data used are primary data and secondary data. Primary data is obtained directly from observations and interviews with informants in the field, while secondary data comes from documents, regulations, and data previously published to data users. The analysis technique was carried out by grouping data, coding, and then presenting a visualization of the results using NVivo 12 plus software. The results of the study found that the ways to improve the quality of UKI at STO are adhering to the Annual Monitoring Plan (RPT) guidelines, increasing the knowledge and soft skills of UKI staff, increasing the use of technology, segregating UKI duties and responsibilities.